2005
DOI: 10.1590/s1678-91992005000200008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a sodium and a calcium channel blocker on lethality of mice injected with the yellow scorpion (Leiurus quinquestriatus) venom

Abstract: Scorpion venom toxins generally produce similar effects by mainly acting on sodium channels, and to a lesser extent, on potassium, calcium, and chloride channels. This leads to increased release of neurotransmitters and mediators, resulting in a cascade of pathological events, involving the central nervous system, the autonomic nervous system, the cardiovascular and the respiratory system, eventually leading to death. The objective of this paper was to discover whether a sodium channel blocker, lidocaine, or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…4C and D), it can be proposed that L-type calcium channels are not engaged in the stimulatory effect of A. bicolor. The same finding was obtained in vivo by Al-Shanawani et al, 2005 who found that verapamil could not protect the mice injected with the venom of L. quinquestriatus.…”
Section: Discussionsupporting
confidence: 79%
“…4C and D), it can be proposed that L-type calcium channels are not engaged in the stimulatory effect of A. bicolor. The same finding was obtained in vivo by Al-Shanawani et al, 2005 who found that verapamil could not protect the mice injected with the venom of L. quinquestriatus.…”
Section: Discussionsupporting
confidence: 79%
“…It is clear that venom-evoked Na + channel activation is the first step in the cascade of events that take place after scorpion envenomation and several studies have demonstrated its efficacy in protecting animals from peripherally injected scorpion venom (Fatani et al, 2000(Fatani et al, , 2010Vital et al, 2002;Al-Shanawani et al, 2005). Moreover, several investigators have shown that several a neurotoxins, including those present in LQQ venom, have higher affinity for peripheral sodium channels than for those of the central nervous system (Hamon et al, 2002;Kopeyan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic manifestations of scorpion venom toxins are due to their ability to act mainly on Na + and to a lesser degree K + and Ca 2+ channels, prolonging depolarization, causing massive release of neurotransmitters and modulators and thus affecting different systems. Treatment with channel blockers have been shown to protect animals from systemic pathological manifestations and lethality of animals injected peripherally with LQQ scorpion venom (Fatani et al, 2000(Fatani et al, , 2010Vital et al, 2002;Al-Shanawani et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with other toxicological reports, which used neurotropic agents that targeted voltagegated sodium channels (VGSCs). Al-Shanawani et al showed that mice pre-treated with lignocaine survived longer after the inoculation of the Leiurus quinquestriatus venom than animals that received only vehicle [1]. The best results were obtained when the mice were treated minutes before the venom inoculation.…”
mentioning
confidence: 99%